2013
DOI: 10.1534/g3.113.006924
|View full text |Cite
|
Sign up to set email alerts
|

Yeast hEST1A/B (SMG5/6)–Like Proteins Contribute to Environment-Sensing Adaptive Gene Expression Responses

Abstract: During its natural life cycle, budding yeast (Saccharomyces cerevisiae) has to adapt to drastically changing environments, but how environmental-sensing pathways are linked to adaptive gene expression changes remains incompletely understood. Here, we describe two closely related yeast hEST1A-B (SMG5-6)–like proteins termed Esl1 and Esl2 that contain a 14-3-3–like domain and a putative PilT N-terminus ribonuclease domain. We found that, unlike their metazoan orthologs, Esl1 and Esl2 were not involved in nonsens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In contrast to these results in worms, we did not observe activation of the UPR when we depleted several different core NMD components in mammalian cells or knocked out the NMD factor UPF3B in vivo (Fig and Supplementary Figs S1A–C and S2). While Sakaki et al showed that depletion of the NMD factor, SMG6, elicits UPR activation in HeLa cells, this may be because of loss of SMG6's non‐NMD functions, such as telomere maintenance . Indeed, Sakaki et al found that knockdown of another NMD factor, SMG1, did not significantly induce the UPR .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these results in worms, we did not observe activation of the UPR when we depleted several different core NMD components in mammalian cells or knocked out the NMD factor UPF3B in vivo (Fig and Supplementary Figs S1A–C and S2). While Sakaki et al showed that depletion of the NMD factor, SMG6, elicits UPR activation in HeLa cells, this may be because of loss of SMG6's non‐NMD functions, such as telomere maintenance . Indeed, Sakaki et al found that knockdown of another NMD factor, SMG1, did not significantly induce the UPR .…”
Section: Resultsmentioning
confidence: 99%
“…We had on hand an additional series of TAP-tagged strains ( RGI1-TAP , HXK1-TAP and HXT7-TAP ) from previous work ( 30 ). To ask if introduction or the TAP-epitope tag was also associated with unexpected transcriptional activity, the strains were grown in respiratory media (YPEG) to induce target gene-expression.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast EST/SMG-like (ESL) proteins, Esl1 and Esl2 share extensive sequence and domain topology similarity with human hEST1A/B and Drosophila and Caenorhabditis elegans SMG5/6 proteins. Importantly, this similarity comprises the region corresponding to the 14-3-3-like Est-one-homology domain and the C-terminal PIN endonuclease domain with complete conservation of critical D/E residues required for nuclease activity of PIN-domain proteins [ 41 ]. In terms of function, Esl1, Esl2 proteins are involved in the expression of a small subset of hexose and amino acid metabolism-related genes via environment-sensing adaptive transcriptional response mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, loss of Esl1/2 combined with loss of either of two different components (Dfg16 and Rim8) of the Rim101 pH sensing pathway causes synthetic lethality in yeast. Interestingly, the subset of genes regulated in response to alkaline conditions overlaps considerably with the response to low iron, perhaps due to lowered solubility of iron at high pH [ 41 ]. In Candida albicans , ferric reductases, FRE2 and FRP1, are regulated by direct interaction with the Rim101p transcriptional factor in alkaline-pH environments [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%